Efektivitas Penggunaan Media Film Pendek sebagai Media Penyuluhan Kesehatan tentang Verbal Bullying terhadap Tingkat Pengetahuan Siswa MTS Munir Ismail Gondanglegi - Titan Aurora Anjini (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2025)
Verbal bullying involves hurtful words, such as insults and degrading nicknames, and remains a growing issue in Indonesia, with 87 cases reported as of August 2023. Health counseling is an approach to addressing this problem, and audiovisual media like short films can enhance adolescents' understanding of such counseling. This study examines the effectiveness of short films as a health education medium on verbal bullying among early adolescents at MTs Munir Ismail Gondanglegi. Using a quantitative pre-experimental pretest-posttest one-group design with simple random sampling, 60 students were selected from a population of 150. A questionnaire measured respondents' knowledge before and after receiving health education through a short film. Wilcoxon signed ranks test analysis showed a significant increase in knowledge, with a mean difference of 3.93 and a p-value of 0.000. These results confirm that short films are an effective medium for improving adolescents' understanding of verbal bullying, making audiovisual approaches valuable in health education.